Preferential charging for government authorised emergency electric vehicles. (3rd February 2020) - Yaqub, Raziq; Shifa, Fahd Ali; Butt, Muhammad Fasih Uddin
The proliferation of Electric Vehicles (EVs) is exponential. However, the power grid is not able to provide simultaneous charging of several EVs due to limited power production capabilities and old distribution infrastructure. Scheduled charging is one of the most advocated solutions. However, it is not viable for emergency vehicles. This paper proposes to provide priority charging service for government authorised emergency EVs. For enablement of this proposal, a complete solution that includes architecture, as well as the protocols suite is suggested. To realise such a service, the paper suggests a major functional entity called a Priority Charging Server, i.e. a database server where authorised emergency EVs' IDs are registered, and their record is maintained. The paper also proposes modifications in the IEC15118 and IEC 61850 protocol suites. These protocols provide communication between vehicle and grid. The solution also inculcates roaming as well as non-roaming scenarios, i.e. a priority charging request may be originated by an authorised emergency EV from a Home Utility Network, as well as Visiting Utility Network. The paper is concluded with a MATLAB-based proof-of-concept simulation.